Virtual Reality and Augmented Reality Technology in Bridge Engineering: A Review - Ho, Thi Lan Huong; Thanh, Nguyen-Chi (Engineering, Technology & Applied Science Research, 2025)
Improving the quality of specialized disciplines within the construction sector is a necessary and inevitable trend. Each field has distinct characteristics, leading to differences in the adoption and application of technologies, which, in turn, drive tailored research approaches. Bridge construction, as a critical subdomain, frequently involves large-scale, complex projects that draw interdisciplinary attention from experts across various fields, extending beyond construction alone. This interdisciplinary nature underscores the importance of advanced technologies for management, design, construction, and communication, particularly in making specialized knowledge accessible and practical for diverse stakeholders. Virtual Reality (VR) and Augmented Reality (AR) have emerged as transformative tools to address these challenges. Despite extensive research on VR and AR in the broader construction industry, studies focused on their application in bridge construction remain limited. This paper consolidates existing research, examining VR and AR in the context of bridge construction. It provides a comprehensive overview of their benefits, challenges, equipment requirements, and emerging trends, providing insight to guide future research and support the practical implementation of VR and AR in this field.